141k views
0 votes
I need to know how to solve for this.

I need to know how to solve for this.-example-1

1 Answer

2 votes

9514 1404 393

Answer:

use the rules of exponents

Explanation:

The applicable rules of exponents are ...

(a^b)(a^c) = a^(b+c)

(a^b)/(a^c) = a^(b-c)

(a^b)^c = a^(bc)

(ab)^c = (a^c)(b^c)

__

Applying these to the left-side expression, we can simplify it so it looks like the right side expression.


((12x^5)(2x^7))/((2x^2)^3)=(12\cdot2x^(5+7))/(2^3x^(2\cdot3))=(24x^(12))/(8x^6)\\\\=3x^(12-6)=\boxed{3x^6}

User Detroyejr
by
5.7k points